Desenvolvimento do bebê : implicações do agenciamento cotidiano e representações sociais na creche - Abreu, Bárbara Cecilia Marques (2023)
In the first 18 months of life, the human being develops at a spectacular speed, and nowadays, the baby spends part of this time in daycare. Thus, the present work has as its theme the development of the baby and the social representations about it, considering the implications in the daily school life, from the point of view of the adults who care for it. In this way, this research sought to answer the following question: In what way does the social representation of the everyday actions of the school of early childhood education, between caring and educating, question the development and constitution of babies? To do so, it was based on a theoretical discussion in a rhizomatic perspective, established in transversality, which sought to ally anthropology, medicine, psychology, psychoanalysis, pedagogy, philosophy, and history to think-research with and about babies. It is characterized as a qualitative, exploratory research, inspired by narrative research. As a procedure, this type of research seeks to focus on a small number of individuals. Therefore, the research was carried out throughout three months, with the collaboration of one teacher and two nursery teachers from a private kindergarten in Porto Alegre, RS, and three families of three babies aged between 15 months and 21 months. The "baby's development journal" was the physical resource used for participation in the research and creation/generation of data along the way. The data analysis was performed from the Content Analysis, from the perspective of Franco, (2018) and Sampaio; Lycarião, (2021). As a priori analysis category, the baby's development was listed. And from the floating reading of the diaries, and the emergence of the latent content, three subcategories were listed, a posteriori: motor development, verbal/oral language and cognitive-affective. The research findings also point out that we are on a path toward the construction of the understanding of the baby as a complete person, but we still have a long way to go. For, when we characterize the adults' perspective about the baby's experience, we find social representations interpellated by scientific knowledge, of a being in development, as well as, of the historical construction of a subject in lack. Therefore, such representations interpellate the way of conceiving, caring, and educating the baby both at school and in the family.